Ex-Vivo Heart Perfusion Machines in DCD Heart Transplantation Model: The State of Art - Chiara Tessari; Giovanni Lucertini; Mariangela Addonizio; Veronica Geatti; Daniela Bacich; Nicola Pradegan; Assunta Fabozzo; Roberto Bianco; Giuseppe Toscano; Vincenzo Tarzia; Gino Gerosa (Transplant International)
The Donation-after-Circulatory-Death (DCD) heart transplantation program increases donor pool but resulting in more serious ischemic-related myocardial injury (IRI), leading to higher incidence of primary graft dysfunction (PGD). Ex-vivo machine perfusion (EVMP) for DCD heart is being considered a useful aid in improving grafts number and quality assessment, aiming to better outcomes. In this review we will analyze the role of EVMP techniques in the context of DCD with special attention to their clinical aims and results and future perspectives. A review of available clinical and pre-clinical studies involving EVMP with DCD donation model was performed. Thirty-four original articles about preclinical studies were found. First studies were designed to evaluate graft function in DCD hearts after EVMP, while recent research focus on possible therapies that could be associated with EVMP. Twenty-one original articles about clinical studies were found with the Organ-Care-System (TransMedics) as MP used. Outcomes, such as survival rates or rejection episodes, are comparable to outcomes from donation-after-brain-death. EVMP in the setting of DCD heart transplantation can be a valid tool for organ preservation and transport. The role of pre-clinical research will be crucial to reduce IRI, achieve organ reconditioning and reduce incidence of PGD.